2020
DOI: 10.1039/d0ra05659f
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a thaumatin-like protein-1 with polyphenol oxidase activity found in Prunus mume

Abstract: Thaumatin-like protein-1 (TLP-1), a protein displaying high polyphenol oxidase (PPO) action and a member of the pathogenesis-related (PR) protein family, has a considerable influence on the enzymatic browning of Prunus mume (Chinese plum).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…et Zucc., popularly known as Chinese plum, is one of the most important seasonal fruits in southern China. Prunus mume is a uniquely flavored, highly acidic yellow or green fruit [1] with a sugar-to-acid ratio of 0.2 [2]. Known as Fructus mume in its unripe state, it is used in traditional medicinal food.…”
Section: Introductionmentioning
confidence: 99%
“…et Zucc., popularly known as Chinese plum, is one of the most important seasonal fruits in southern China. Prunus mume is a uniquely flavored, highly acidic yellow or green fruit [1] with a sugar-to-acid ratio of 0.2 [2]. Known as Fructus mume in its unripe state, it is used in traditional medicinal food.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ‘Yunnan figleaf gourd’-grafted cucumber seedlings up-regulated miR397a expression, which was predicted to target several chilling stress-related genes, including LAC4 , LAC11 , LAC17 and Thaumatin-like protein 1 ( TLP1) . TLP1 is a high polyphenol oxidase (PPO) protein that can act as an antifreeze protein to improve chilling tolerance in plants [ 42 44 ]. Some studies have shown that miR398 is down-regulated by chilling stress, and it regulates intracellular ROS content by modulating CSD1 and CSD2 [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to differences in the charges of different proteins, their binding abilities to ion exchangers also vary, resulting in different orders of elution into the solution [60]. The resins, which have been used for ion exchange chromatography in the purification of PPO, are DEAE-cellulose [61] and UNOsphere™ Q (BioRad, Hercules, CA, USA) [62]. The pH of the buffer solution for both DEAE and Q ion exchange chromatography needs to be at least one unit higher than the pI of the target protein to be bound, where the pH of the buffer solution for Q ion exchange chromatography is higher than that of DEAE.…”
Section: Ion Exchange Chromatographymentioning
confidence: 99%